PELATIHAN BUDIDAYA MAGGOT UNTUK MENGURANGI LIMBAH BUDIDAYA BAWANG MERAH - Pratiwi, Destyana Ellingga; Nugroho, Condro Puspo; Permanasari, Paramyta Nila; Utomo, Medea Rahmadhani; Dani, Muhammad Aufaa; Amilia, Nurdiana (Abdi Panca Marga, 2024)
Improper handling of organic waste can have a negative impact on human health and pollute the environment. One solution for utilizing organic waste is through maggot cultivation. Through maggot cultivation, negative impacts and the amount of organic waste can be minimized. Apart from that, maggot cultivation can increase the added value of organic waste, especially as poultry feed so that it can increase the weight of poultry. This community service activity aims to introduce the shallot farming community in Gending District, Probolinggo Regency about how to raise maggots by utilizing shallot skin waste which is always abundant every shallot season. This activity is expected to increase farmers' income, reduce waste (zero waste) remaining from shallot production, and reduce the negative impact of organic waste on the environment. References Fauzi, R.U. & Sari, E.R. (2018). Analisis usaha budidaya maggot sebagai alternatif pakan lele. Jurnal Teknologi dan Manajemen Agroindustri, 7(1), 39−46. Fonseca, K., Dicke, M., & Van, L. J. (2017). Nutritional value of the Black Soldier Fly (Hermetia illucens L.) and its suitability as animal feed. Journal of Insects as Food and Feed, 3(2), 105−120. Sastro, Y. (2016). Teknologi pengomposan limbah organik kota menggunakan Black Soldier Fly. Jakarta: Balai Pengkajian Teknologi Pertanian (BPTP). Tomberlin, J. K., Adler, P. H., & Myers, H. M. (2018). Development of the Black Soldier Fly (Diptera: Strationmyidae) relation to temperature. Environmental Entamol, 38, 930−934